IMPROVING LISTENING SKILL OF STUDENTS USING METACOGNITIVE INSTRUCTION - Ida Nurhidayah; Nadiah Ma’mun (IJET (Indonesian Journal of English Teaching), 2016)
This study is aimed to describe the implementation of metacognitive instruction and to improve students’ listening ability on TOEFL listening comprehension section by using metacognitive instruction at the second semester students of English Education Department of Walisongo State Islamic University Semarang in the academic year of 2015/2016 and to know the enhancement of students’ listening ability on TOEFL listening comprehension section after being taught using metacognitive instruction. The design of this study is classroom action research that was conducted in two cycles with four activities in each cycle, they are planning, acting, observing, reflecting. Pre-cycle was also done before this study was conducted. The result of this study showed that using metacognitive instruction could improve students’ listening ability on TOEFL listening comprehension section. This was proved by the enhancement of students’ test result that improved in every cycle. The result of the study also showed that metacognitive instruction could improve the students’ listening ability on TOEFL listening comprehension section.